2022
DOI: 10.14686/buefad.777974
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 21st Century Skills Training on Foreign Language Teachers’ Perceptions Regarding Their Educational Technology and Materials Development Competencies

Abstract: The effect of 21st century skills training on foreign language teachers' perceptions regarding their educational technology and materials development competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Kaçar (2020) also, in his study with 190 teachers of English, revealed that teachers who participated in a training on 21st century skills had a more positive perception of 21st century innovation skills than those who did not. Furthermore, an experimental study conducted by Yeni (2018) with the participation of 33 teachers of English showed that teachers' practices and perceptions of the 21st century changed positively after they received training on 21st century skills. The results are not unexpected because professional development, as noted by Jackson and Andrew (2000), is a crucial tool that teachers can engage in both inside and outside of the school setting to expand their knowledge, understanding, and practice of these skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaçar (2020) also, in his study with 190 teachers of English, revealed that teachers who participated in a training on 21st century skills had a more positive perception of 21st century innovation skills than those who did not. Furthermore, an experimental study conducted by Yeni (2018) with the participation of 33 teachers of English showed that teachers' practices and perceptions of the 21st century changed positively after they received training on 21st century skills. The results are not unexpected because professional development, as noted by Jackson and Andrew (2000), is a crucial tool that teachers can engage in both inside and outside of the school setting to expand their knowledge, understanding, and practice of these skills.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies investigating 21st century skills in the field of English language teaching have focused on either the books if they include these skills (Akçay, 2019;Elgün, 2021) or the lecturers at university (Demirkol-Orak & İnözü, 2021;Ekinci, 2019;). Others have investigated teachers' 21st century skills practices at all levels, not specifically secondary school English language teachers (Eker, 2020;Kaçar, 2020;Otlu, 2020;Şahin, 2021;Yeni, 2018). In addition, although MoNE has made some adjustments to the curriculum and the qualifications of teachers to keep up with the age, there is not enough evidence on teachers' current practices.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, language education should prepare students for rapidly changing economic, political, and social conditions and develop their twenty-first-century skills in the ever-changing realities of a globalized society (Moeller and Abbott, 2018;Quicios, 2018). Yeni's (2018) found that twenty-first-century skills increased the educational technology and material development competencies of foreign language teachers.…”
Section: Learning Technologies In Foreign Language Educationmentioning
confidence: 99%
“…Additionally, technology enables personalization of learning, where learning approaches can be tailored to individual needs, optimizing understanding and retention of information. Apart from providing critical digital skills, the use of technology also prepares oneself to face the challenges of a future that is increasingly connected and dependent on technological innovation (Yeni, 2022).…”
Section: Introductionmentioning
confidence: 99%